Early Sirolimus Gel Treatment May Diminish Angiofibromas and Prevent Angiofibroma Recurrence in Children With Tuberous Sclerosis Complex - Okanishi, Tohru; Fujimoto, Ayataka; Enoki, Hideo; Ogai, Masaaki (Frontiers in Medicine, 2020)
Introduction: Tuberous sclerosis complex (TSC) is a multisystem neurocutaneous disorder. Angiofibromas (AF), fibrous plaques, and hypopigmented macules are the major skin findings in TSC. Topical sirolimus reduces the volume and redness of AF and other skin findings. However, the efficacy of early intervention and long-term treatment remains to be clarified. We investigated the efficacy of sirolimus gel for AF in children with TSC. Methods: We recruited nine children (five boys; four girls) with TSC and AF. We used 0.2% sirolimus gel over 6 months. We reviewed each patient’s medical records and photographs for clinical information and data related to improvements in skin lesions. We evaluated the size of AF, fibrous plaques, and color changes in AF and hypopigmented macules. Results: Age at the initiation of treatment ranged from 3.5 to 11.0 years. The follow-up period ranged from 6 to 36 months (≥24 months in 3 children). Patients presented with papular AF (9), miliary AF (8), AF redness (9), fibrous plaques (5), and hypopigmented macules (2). After 6 months of treatment, improvement of AF size and redness was seen in all nine patients. Patients treated for ≥24 months showed significant decrease in AF size that persisted until the final follow-up. Gradual improvement in fibrous plaques was observed, and marked reduction in size was achieved by 4-18 months. Conclusion: Early sirolimus gel intervention is effective for the treatment of AF and fibrous plaques in children with TSC. Early intervention with sirolimus gel may maintain the skin at near-normal levels in patients with TSC.